Analisis Yuridis Unsur Dolus dalam Delik Gratifikasi dan Akibat Hukumnya Berdasarkan Undang-Undang Nomor 20 Tahun 2001 (Putusan No. 2205 K/Pid.Sus/2022) - Hendra, Muhammad (Peneliti.net, 2024)
Corruption is a criminal act that is an extraordinary scourge of a country where the consequences are not only detrimental to the country but also hamper development in that country. In Supreme Court decision no. 2205 K/Pid.Sus/2022, a person caught in a corruption case decided to go free on the pretext that there was no agreement between the gratification and the person who received it. This research aims to find out how the dolus element is applied in the offense of gratification based on the Corruption Law. The research method used in this research is a normative juridical approach, namely research that analyzes statutory regulations and how they are implemented. The results of this research indicate that the application of dolus in gratification offenses is based on Law no. 20 of 2001 Amendment to Law no. 31 of 1999 concerning the Eradication of Corruption Crimes in Decision No. 2205 K/Pid.Sus/2022 lies in the existence of an agreement (meeting of minds) between the two parties as regulated in Article 5 paragraph (1) and in this case no evidence of such agreement was found.